Legal Policy on Changes to Copyright Law in the Digital Space: Politik Hukum Atas Perubahan Undang-Undang Hak Cipta di Ruang Digital - Romandelas Manurung; Gunardi Lie (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Indonesia's rapid digital transformation has reshaped the creation, distribution, and use of copyrighted works, intensifying the urgency for adaptive legal protection. Specific Background: Despite the 2014 Copyright Law addressing digital elements, its provisions remain insufficient to manage algorithm-driven, cross-border infringements proliferating on user-generated content platforms. Knowledge Gap: Existing regulations have not fully anticipated technological developments nor clearly defined the responsibilities of digital platform operators, especially after the Constitutional Court’s reinterpretation of liability under Article 10. Aims: This study examines the legal politics underlying the amendment of the Copyright Law to strengthen protection mechanisms in the digital environment. Results: Findings reveal the need for more responsive regulation, expanded obligations for digital platforms, harmonized protection of moral and economic rights, and enhanced enforcement tools, including integrated digital surveillance and more effective access-blocking procedures. Novelty: The study offers a conceptual model that links legislation theory with legal protection theory to propose an adaptive copyright protection framework suited to digital-era challenges. Implications: These insights provide strategic direction for policymakers in formulating reforms that ensure legal certainty, fairness, and public benefit within Indonesia’s evolving digital copyright ecosystem. Highlights: The digital environment demands stronger, adaptive copyright protection responsive to technological change. Constitutional Court Decision No. 84/PUU-XXI/2023 expands platform liability, revealing gaps in current regulation. A revised legal framework must integrate surveillance, platform obligations, and balanced protection of creators’ rights. Keywords: Copyright Law, Digital Platforms, Legal Politics, Enforcement, Regulation